The Canonical Correlation Analysis of Technology Acceptance KASETTRACT and Members' Usage Intentions of Brackish Water Durian from Mega Farm Enterprise - Chanamool, Nalinee; Kumyat, Anchana; Nunthasen, Ke (Arts of Management Journal, 2024)
The purpose of this study was to analyze the canonical relationship of technology acceptance and intention to use KASETTRACK application technology including to study the problems and obstacles to numbers use of KASETTRACK. There is mixed methods research, the respondents included 50 members of Brackish water durian mega farm enterprise to in-depth interviews and to focus on groups of 15 persons which is from Pearson correlation statistics and canonical correlation method. The results showed that there was a correlation between the set of canonical variables of technology acceptance and intention to use (Rc) = 0.90085, the weight of the variable set of technology acceptance is between 0.05294 – 0.07181 and the weight of the variable set of technology intention is between 0.00488 – 0.17694. The management approach is that the promotion organization and the Group Chairman should continuously monitor the usage of KASETTRACK application technology among members to acknowledge problems/ obstacles in use and discover that it should be integrated with relevant agencies. The group members were engaged in educating, training, technology transferring and monitoring the utilization of information to mitigate the obstacles or (critical points) concerns that will be affected an acceptance and intention to use the technology. Objective is to encourage the members for continuing utilization of the technology.